Degradation Evaluation of HDPE in Oil and Gas Pipelines using Electrochemical Impedance Spectroscopy Technique - Khalid, H.U. (Institute of Electrical and Electronics Engineers Inc., 2020)
Non-metallic pipes (NMP) are used as an internal lining and standalone pipes as a mitigation plan to preserve the safety and integrity of the pipeline systems. However, these NMP, especially polymers, lose their functionality with time in the environment having CO2, H2S, high temperature, and pressure due to the permeation process. The monitoring of damage mechanism due to permeation is ill-defined in the oil and gas industry, which results in uncertainty in asset integrity management. The main goal of this research project is to evaluate the different degradation stages of HDPE due to permeation through the application of dielectric properties. The purpose is to correlate the dielectric properties with the impedance data obtained from the EIS technique. The methodology comprises of the accelerated aging of the High-Density Polyethylene (HDPE) polymeric material in the autoclave equipment. Then the evaluation of dielectric properties will be carried out by EIS. The material has a thickness of 3 mm and will be used in the square shape for these experiments. The expected results of this project will be in terms of dielectric properties correlating with impedance data. Â© 2020 IEEE.